Economic cost associated with democratic transition economic analysis of Egypt - Khalifa, Sarah Refaat (AUC Knowledge Fountain, 2017)
The modern world has passed through waves of democratic transition where citizens of certain countries were not satisfied with their governing models. There was no definite cause why people would rebel against their governments. There were cases of poverty and economic deterioration, suppression of freedom, political inequity, or police and military domination. Egypt has faced all of them simultaneously, resulting in the 2011 revolutionary wave. Since 2011, Egypt has been trembling in the democratic transition period. This study is concerned with shedding the light on Egypt’s economic indicators from 2011 till 2015. It analyzes the results of the wave on the economy, with major sectors having been affected. There will be a closer look on GDP, foreign reserves, income from the Suez Canal, and a balance of trade. The Egyptian economy is clearly affected by the revolutionary wave which has dragged down the foreign reserves to unprecedented decline, and depreciated the L.E. currency to its lowest value. In 2016, the Egyptian economy is struggling to go up to the same point where it was in 2011, to be restored and able to revive.